Monitoring the impact of a national school based deworming programme on soil-transmitted helminths in Kenya: the first three years, 2012 – 2014. Issue 1 (December 2016) - Okoyo, Collins; Nikolay, Birgit; Kihara, Jimmy; Simiyu, Elses; Garn, Joshua; Freeman, Mathew; Mwanje, Mariam; Mukoko, Dunstan; Brooker, Simon; Pullan, Rachel; Njenga, Sammy; Mwandawiro, Charles
Abstract Background In 2012, the Kenyan Ministries of Health and of Education began a programme to deworm all school-age children living in areas at high risk of soil-transmitted helminths (STH) and schistosome infections. The impact of this school-based mass drug administration (MDA) programme in Kenya is monitored by the Kenya Medical Research Institute (KEMRI) as part of a five-year (2012–2017) study. This article focuses on the impact of MDA on STH infections and presents the overall achieved reductions from baseline to mid-term, as well as yearly patterns of reductions and subsequent re-infections per school community. Methods The study involved a series of pre- and post-intervention, repeat cross-sectional surveys in a representative, stratified, two-stage sample of schools across Kenya. The programme contained two tiers of monitoring; a national baseline and mid-term survey including 200 schools, and surveys conducted among 60 schools pre- and post-intervention. Stool samples were collected from randomly selected school children and tested for helminth infections using Kato-Katz technique. The prevalence and mean intensity of each helminth species were calculated at the school and county levels and 95 % confidence intervals (CIs) were obtained by binomial and negative binomial regression, respectively, taking into account clustering by schools. Results The overall prevalence of STH infection at baseline was 32.3 % (hookworms: 15.4 %;Ascaris lumbricoides : 18.1 %; andTrichuris trichiura : 6.7 %). After two rounds of MDA, the overall prevalence of STH had reduced to 16.4 % (hookworms: 2.3 %;A. lumbricoides : 11.9 %; andT. trichiura : 4.5 %). The relative reductions of moderate to heavy intensity of infections were 33.7 % (STH combined), 77.3 % (hookworms) and 33.9 % (A. lumbricoides ). ForT. trichiura, however, moderate to heavy intensity of infections increased non-significantly by 18.0 % from baseline to mid-term survey. Conclusion The school-based deworming programme has substantially reduced STH infections, but because of ongoing transmission additional strategies may be required to achieve a sustained interruption of transmission.